2014
DOI: 10.1002/fsn3.85
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant, antimicrobial and cytotoxic activities of Tagetes minuta and Ocimum basilicum essential oils

Abstract: Chemical composition, antioxidant, antimicrobial and cytotoxic activities of Tagetes minuta (TM) essential oil (TMO) and Ocimum basilicum (OB) essential oil (OBO) were examined. The main components for TMO were dihydrotagetone (33.9%), E-ocimene (19.9%), tagetone (16.1%), cis-β-ocimene (7.9%), Z-ocimene (5.3%), limonene (3.1%) and epoxyocimene (2.03%). The main components for OBO were methylchavicol (46.9%), geranial (19.1%), neral (15.15%), geraniol (3.0%), nerol (3.0%), caryophyllene (2.4%). Inhibitory conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 56 publications
1
63
2
7
Order By: Relevance
“…In India, it is found growing along road-sides and wastelands in the regions of Northern plains and Western Himalayas including Solan, Himachal Pradesh, India and adjoining areas. Numerous reports have appeared on chemical composition of its essential oil (Chamorro et al, 2008;Breme et al, 2009;Meshkatalsadat et al, 2010;Shahzadi et al, 2010;Shirazi et al, 2014) but no information has been reported on the comparative allelopathic impact of T. minuta oil in relation to its major component cis-β-ocimene. Thus present study was designed to explore the allelopathic potential of oil in comparison to cis-β-ocimene on growth of Cassia occidentalis (Family Fabaceae), a wasteland weed.…”
Section: Introductionmentioning
confidence: 99%
“…In India, it is found growing along road-sides and wastelands in the regions of Northern plains and Western Himalayas including Solan, Himachal Pradesh, India and adjoining areas. Numerous reports have appeared on chemical composition of its essential oil (Chamorro et al, 2008;Breme et al, 2009;Meshkatalsadat et al, 2010;Shahzadi et al, 2010;Shirazi et al, 2014) but no information has been reported on the comparative allelopathic impact of T. minuta oil in relation to its major component cis-β-ocimene. Thus present study was designed to explore the allelopathic potential of oil in comparison to cis-β-ocimene on growth of Cassia occidentalis (Family Fabaceae), a wasteland weed.…”
Section: Introductionmentioning
confidence: 99%
“…Synergistically, essential oils with antimicrobial effects has the ability to disrupt lipid structure of the cell wall of bacteria, leading to destruction of cell membrane, cytoplasmic leakage, lysis of the cell, and ultimately cell death [22]. The results of the present work indicated that if the chemical composition and concentration of the essential oils were suitable the elimination or reduction of the bacterial population would occur regardless of the character gram.…”
Section: Discussionmentioning
confidence: 66%
“…Although the constituents of essential oils can act as antioxidants, they may also act as prooxidants and affect inner cell membranes. Depending on the type and concentration, this effect may result in cellular cytotoxicity [22,26]. Components of natural products especially volatile terpenes and phenolic components which show antioxidant activity, can be oxidized by ROS and thus generate additional radical species like panoxyl, hydroxyl and superoxide radicals and hydrogen peroxide and affect the cellular redox status in the so-called "antioxidative stress" [27].…”
Section: Discussionmentioning
confidence: 99%
“…The extract of O. basilicum showed moderate activity against G. lamblia (Table 2), which supports its use in traditional medicine to treat gastrointestinal disorders (Shirazi et al, 2014). Recently, the essential oil of O. basilicum and two of its main components (linalool and eugenol) were reported to inhibit the growth of G. lamblia in vitro (Almeida et al, 2007).…”
Section: Antiprotozoal Activitymentioning
confidence: 67%